Queen Charlotte’s Use of Directive Speech Acts in Netflix’s Queen Charlotte: A Bridgerton Story (2023) - Chaterine Evelyna Paramesti Kirana; Anna Dewanti; Lilla Musyahda (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study explores how Queen Charlotte’s utterances in directive speech acts reflect empowerment as a Black woman leader through Netflix’s Queen Charlotte: A Bridgerton Story (2023). This research used a qualitative method. The source of data in this research consists of six episodes, each featuring a transcript from the movie series. The examination of Queen Charlotte’s utterances showed a total of 61 directive speech acts classified by Kreidler (1998): Commands occurred 48 times (78.6%), Requests 11 times (18%), and Suggestions 2 times (3.2%). Using Simpson and Mayr’s (2019) categorization of “power and talk,” 46 of the 61 directive speech acts were found with power characteristics: Topic Control (71.7%), Enforcing Explicitness (17.3%), and Interruption (10.8%). These findings demonstrate that directive speech acts may appear as a form of power that reflects identity and empowerment, especially in the speech of Black women leaders. Queen Charlotte's speaking patterns effectively convey her power, capability, and resistance to being made invisible.